Synonymy of Reikosiella Yoshimoto under Merostenus Walker (Hymenoptera: Chalcidoidea: Eupelmidae), with a checklist of world species and a revision of those species with brachypterous females - Gibson, Gary A. P. (Zootaxa, 2017)
Reikosiella Yoshimoto, 1969 is synonymized under Merostenus Walker, 1837 n. syn. and treated as M. (Reikosiella), one of four subgenera recognized in the genus. Hirticauda Bouček, 1988, previously treated as a subgenus of Reikosiella, is synonymized under M. (Merostenus) n. syn., and two subgenera established in Reikosiella by Gibson (1995) are synonymized under Merostenus and treated as the subgenera M. (Capreocauda) and M. (Incohata) n. syns. The new generic synonymy is proposed after morphological comparison of females and males of Merostenus and Reikosiella sensu Gibson (1995), including reanalysis of features possessed by a basal group of genera of Eupelminae whose females share two hypothesized symplesiomorphies—a medially divided mesotrochantinal plate and lack of a mesotibial apical groove. A checklist of the 51 world species assigned to Merostenus is given, with 1 described species in M. (Incohata), 6 in M. (Capreocauda), 6 in M. (Reikosiella) and 38 in M. (Merostenus). All but one, the type species of Merostenus, represent new combinations. The species of Merostenus with brachypterous females are revised, with 8 of 10 species described as new. In addition to M. (Merostenus) excavatus (Dalman) (♀, ♂) from the Palaearctic, described in the same subgenus are one new species from Mexico, M. (Merostenus) mexicanus n. sp. (♀), and seven from the Afrotropical region, M. (Merostenus) distigma n. sp. (♀: Kenya, Tanzania), M. (Merostenus) micropterus n. sp. (♀: Democratic Republic of the Congo), M. (Merostenus) platyscapus n. sp. (♀: South Africa), M. (Merostenus) reticulatus n. sp. (♀, ♂: Kenya), M. (Merostenus) speculum n. sp. (♀: Burundi), M. (Merostenus) congoensis (♀: Democratic Republic of the Congo), and M. (Merostenus) longistylus n. sp. (♀, ♂: South Africa). The first seven species are assigned to the excavatus species-group of M. (Merostenus) based on females sharing a completely sclerotized pronotum and apically truncate syntergum. Also treated is M. (Reikosiella) melinus (Yoshimoto) n. comb. (♀: Argentina, Brazil, Hawaii), the only species known with macropterous to variably strongly brachypterous females. Six species are transferred to other genera. Merostenus ferrugineus Yoshimoto & Ishii is transferred to Anastatus Motschulsky as A. ferrugineus (Yoshimoto & Ishii) n. comb., Merostenus guamensis Yoshimoto & Ishii and Merostenus palauensis Yoshimoto & Ishii are transferred to Eupelmus Dalman and provisionally classified in E. (Eupelmus) as E. (Eupelmus) guamensis (Yoshimoto & Ishii) n. comb. and E. (Eupelmus) palauensis (Yoshimoto & Ishii) n. comb., Eupelminus subapterus Ashmead is transferred to E. (Eupelmus) as E. (Eupelmus) subapterus (Ashmead) n. comb., and Eupelminus robustus Brues and Eupelminus tarsatus Waterston are transferred to Arachnophaga (Parasolindenia Brues) as Arachnophaga (Parasolindenia) robusta (Brues) n. comb. and Arachnophaga (Parasolindenia) tarsata (Waterston) n. comb. The character-state analysis and treated species are illustrated through macrophotography and, except for A. robusta, notes and illustrations provided for the excluded species to assist their future recognition.